Recycled water absorbent resin composition and method for manufacturing recycled water absorbent resin composition
Patent Information
- Application Number
- JP2023124936
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0011】 本発明の一実施形態に係るリサイクル吸水性樹脂組成物は、臭気の発生、色目の悪化および吸水性能の悪化が発生し難く、かつ、耐尿性の悪化および水可溶性成分量の増大も発生し難いとの効果を奏する。また、本発明の一実施形態に係るリサイクル吸水性樹脂組成物の製造方法は、臭気の発生、色目の悪化および吸水性能の悪化が発生し難く、かつ、耐尿性の悪化および水可溶性成分量の増大も発生し難いリサイクル吸水性樹脂組成物を製造できるとの効果を奏する。
Smart Images

Figure 2025021174000001 
Figure 2025021174000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a recycled water-absorbent resin composition and a method for producing the recycled water-absorbent resin composition. [Background technology]
[0002] In recent years, absorbent resins have been widely used as water absorbents in absorbent articles such as paper diapers, sanitary napkins, and incontinence pads, from the viewpoint of absorbing body fluids. Examples of such absorbent resins include hydrolyzates of starch-acrylonitrile graft copolymers, neutralized products of starch-acrylic acid graft polymers, saponified products of vinyl acetate-acrylic acid ester copolymers, and crosslinked products of partially neutralized acrylic acid polymers. From the viewpoint of water absorption performance, polyacrylic acid (salt)-based absorbent resins using acrylic acid and / or its salt as a monomer are most widely produced industrially.
[0003] Although absorbent articles are generally disposable, interest in recycling absorbent articles and water-absorbing resins is growing due to the rise in environmental awareness. Various methods have been developed as methods for recycling absorbent articles and water-absorbing resins. Examples of the recycling methods include a method in which a used water-absorbing resin containing an absorbed liquid is subjected to a process for discharging the absorbed liquid, such as a washing process and a dehydration process, to obtain a recycled water-absorbing resin (Patent Documents 1 to 4), and a method in which a decomposition product obtained by decomposing a used water-absorbing resin is used as a part of a raw material to produce a water-absorbing resin (recycled water-absorbing resin) (Patent Documents 5 to 18).
[0004] In addition, the recycled water absorbent resin obtained by the above-mentioned method may have problems such as odor generation, deterioration in color due to yellowing, and reduced water absorption performance, which are caused by the remaining absorbed liquid, etc. In order to solve the above problems, various treatment techniques have been developed for the recycled water absorbent resin, such as bleaching treatment (Patent Document 19), treatment with an alkali metal (Patent Document 20), treatment with a polyvalent metal salt followed by treatment with an alkali metal (Patent Document 21), and treatment of contacting another super absorbent resin with the recycled water absorbent resin to further discharge the remaining absorbed liquid from the recycled water absorbent resin (Patent Document 22). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2003-326161 A [Patent Document 2] International Publication No. WO2021 / 162082 [Patent Document 3] International Publication No. WO2021 / 075506 [Patent Document 4] Korean Patent Publication No. 10-2020-0073752 [Patent Document 5] JP 2019-131789 A [Patent Document 6] International Publication No. WO2021 / 162071 [Patent Document 7] International Publication No. WO2020 / 213298 [Patent Document 8] International Publication No. WO2022 / 080342 [Patent Document 9] JP 2023-038963 A [Patent Document 10] JP 2023-038978 A [Patent Document 11] JP 2023-039009 A [Patent Document 12] JP 2023-507864 A [Patent Document 13] U.S. Patent Publication No. 2021 / 0053028 [Patent Document 14] U.S. Patent Publication No. 2021 / 0054161 [Patent Document 15] International Publication No. WO2022 / 081451 [Patent Document 16] International Publication No. WO2022 / 081523 [Patent Document 17] International Publication No. WO2022 / 183184 [Patent Document 18] JP 2020-049398 A [Patent Document 19] International Publication No. WO2020 / 241025 [Patent Document 20] International Publication No. WO2019 / 151538 [Patent Document 21] International Publication No. WO2023 / 007871 [Patent Document 22] International Publication No. WO2021 / 205780 Summary of the Invention [Problem to be solved by the invention]
[0006] On the other hand, when the above-mentioned various treatments are carried out to solve the above-mentioned problems, other problems such as deterioration of urine resistance and increase in the amount of water-soluble components may occur in the recycled water-absorbent resin.
[0007] The present invention aims to solve the above problem without causing the other problem. In detail, the object of the present invention is to provide a recycled water absorbent resin which is prevented from generating odor, from deteriorating color and from deteriorating water absorption performance, and which is also prevented from deteriorating urine resistance and from increasing the amount of water-soluble components. [Means for solving the problem]
[0008] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by mixing adsorbent particles such as activated carbon with the recycled water absorbent resin instead of carrying out the above-mentioned treatment, and have arrived at the present invention.
[0009] One embodiment of the present invention is a recycled water-absorbent resin composition comprising a recycled water-absorbent resin containing used water-absorbent resin and / or a solubilized product thereof as at least a part of the raw material, and adsorbent particles.
[0010] Another embodiment of the present invention is a method for producing a recycled water absorbent resin composition according to one embodiment of the present invention, which includes a mixing step of mixing the recycled water absorbent resin with the adsorbent particles. Effect of the Invention
[0011] The recycled water absorbent resin composition according to one embodiment of the present invention has the effect of being less susceptible to odor generation, deterioration in color, and deterioration in water absorption performance, and is also less susceptible to deterioration in urine resistance and an increase in the amount of water soluble components. Also, the manufacturing method for a recycled water absorbent resin composition according to one embodiment of the present invention has the effect of being able to manufacture a recycled water absorbent resin composition that is less susceptible to odor generation, deterioration in color, and deterioration in water absorption performance, and is also less susceptible to deterioration in urine resistance and an increase in the amount of water soluble components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited thereto, and various modifications are possible within the scope described, and the technical scope of the present invention also includes embodiments obtained by appropriately combining the technical means disclosed in the different embodiments. Note that "acid (salt)" means "acid and / or its salt," and "(meth)acrylic" means "acrylic and / or methacrylic." Furthermore, the mass of the water-absorbent resin is expressed as a value converted into a solid content unless otherwise specified.
[0013] In this specification, "EDANA" is an abbreviation for European Disposables and Nonwovens Associations. Also, "ERT" is an abbreviation for EDANA Recommended Test Methods, a European standard (almost a global standard) for measuring water-absorbent resins. In one embodiment of the present invention, unless otherwise specified, the physical properties of the water-absorbent resin are measured in accordance with the original ERT (revised in 2002 / publicly known document).
[0014] 1. Technical Concept of the Present Invention In order to solve the above problem, when the recycled water absorbent resin is subjected to various treatments disclosed in, for example, Patent Documents 19 to 22, the internal structure of the recycled water absorbent resin may be destroyed by the various treatments. In addition, chemicals such as bleaching agents used in the various treatments may adversely affect the properties of the recycled water absorbent resin, such as urine resistance and the amount of water-soluble components. For these reasons, it is considered that the above-mentioned other problems may occur when the recycled water absorbent resin is subjected to the various treatments.
[0015] On the other hand, the present inventors have found that when adsorbent particles are mixed with a recycled water absorbent resin, the adsorbent particles can improve the color (yellowing) of the recycled water absorbent resin without adversely affecting the internal structure and characteristics of the recycled water absorbent resin, and can also adsorb odorous components derived from trace amounts of urine components remaining in the recycled water absorbent resin. If a large amount of bleach is used for the purpose of improving the color of the recycled water absorbent resin, the color is improved, but it has an adverse effect on the crosslinked structure of the recycled water absorbent resin, and as a result, there is a risk of a decrease in water absorption performance and a decrease in urine resistance due to an increase in the amount of water-soluble components. On the other hand, the present inventors have found a technical idea that the adsorbent particles of the present application can improve the color and odor without causing these problems. Based on the above, the present inventors have conceived the present invention.
[0016] 2. Recycled water-absorbent resin composition of the present invention A recycled water absorbent resin composition according to one embodiment of the present invention (hereinafter referred to as "recycled water absorbent resin composition of the present invention") contains a recycled water absorbent resin containing a used water absorbent resin and / or a solubilized product thereof as at least a part of a raw material, and adsorbent particles. The recycled water absorbent resin composition of the present invention can be produced by using a "production method of a recycled water absorbent resin composition" according to one embodiment of the present invention described later.
[0017] The recycled water absorbent resin composition of the present invention includes a recycled water absorbent resin and adsorbent particles. In addition, since the recycled water absorbent resin uses used water absorbent resin and / or its solubilized product as at least a part of the raw material, it contains a small amount of odorous components derived from human waste components and the like contained in the absorbed liquid. Therefore, as described in the above section [1. Technical Concept of the Present Invention], in the recycled water absorbent resin composition of the present invention, the odorous components are adsorbed by the adsorbent particles without adversely affecting the internal structure and characteristics of the recycled water absorbent resin. That is, the recycled water absorbent resin composition of the present invention has an effect of being less likely to generate odor because it adsorbs odorous components derived from human waste components and the like contained in the absorbed liquid and does not discharge them to the outside. In addition, the adsorbent particles also adsorb components such as human waste components that cause deterioration of the color of the recycled water absorbent resin, thereby having an effect of making the color less likely to deteriorate. Furthermore, the recycled water absorbent resin composition of the present invention has an effect of improving the color and odor described above without using a large amount of bleach. Furthermore, the present invention has the effect that the internal structure and characteristics of the recycled water absorbent resin are not adversely affected, and therefore deterioration of urine resistance and increase in the amount of water-soluble components are unlikely to occur.
[0018] Each of the members constituting the water-absorbing resin composition of the present invention will be described below.
[0019] [2-1. Water-absorbing resin] In one embodiment of the present invention, the "water-absorbent resin" is a water-swellable, water-insoluble polymer gelling agent, and refers to a conventional water-absorbent resin having a water absorption capacity of 10 to 1000 times, although it is not particularly limited thereto. More specifically, the water-absorbent resin before absorbing the liquid to be absorbed (hereinafter also referred to as "initial water-absorbent resin") preferably satisfies the physical property of CRC of 5 g / g or more as "water-swellable" specified in ERT441.2-02, and satisfies the physical property of Ext (amount of water-soluble component) of 0 mass% to 50 mass% as "water-insoluble" specified in ERT470.2-02.
[0020] The water-absorbing resin includes a polymer having a partially neutralized carboxyl group. Specific examples of the water-absorbing resin include polyacrylic acid (salt)-based resins, polysulfonic acid (salt)-based resins, maleic anhydride (salt)-based resins, polyacrylamide-based resins, polyvinyl alcohol-based resins, polyethylene oxide-based resins, polyaspartic acid (salt)-based resins, polyglutamic acid (salt)-based resins, polyalginic acid (salt)-based resins, starch-based resins, cellulose-based resins, (meth)acrylate crosslinked polymers, saponified crosslinked products of (meth)acrylate-vinyl acetate copolymers, starch-acrylate graft polymers and crosslinked products thereof.
[0021] [2-2. Absorbent articles] In one embodiment of the present invention, the term "absorbent article" refers to an article used for absorbing water. An example of the "absorbent article" is an absorbent article comprising an absorbent body containing a water-absorbing resin and a fibrous material, a top sheet having liquid permeability, and a back sheet having liquid impermeability. The absorbent body is preferably manufactured by blending a water-absorbing resin with a fibrous material, or by sandwiching a water-absorbing resin between fibrous materials and molding the mixture into a film, a tube, a sheet, or other shape. Here, examples of the fibrous material include hydrophilic fibers such as crushed wood pulp, cotton linters, crosslinked cellulose fibers, rayon, cotton, wool, acetate, vinylon, and the like. Specific examples of the "absorbent article" include sanitary materials (sanitary products) such as paper diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets, but are not limited thereto.
[0022] [2-3. Used absorbent articles] In one embodiment of the present invention, the term "used absorbent article" refers to an absorbent article that has absorbed absorbed liquid. The used absorbent article may in particular be a used sanitary material that has absorbed body fluids such as urine or blood as the absorbed liquid. Examples of the sanitary material include sanitary materials (sanitary products) such as disposable diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets.
[0023] [2-4. Used water-absorbent resin and its solubilized matter] In one embodiment of the present invention, the term "used water absorbent resin" refers to the water absorbent resin contained in the used absorbent article. The used water absorbent resin absorbs the absorbed liquid and is usually in the form of a hydrogel with the absorbed liquid taken in. In one embodiment of the present invention, the term "solubilized product of used water absorbent resin (hereinafter simply referred to as "solubilized product")" refers to a product obtained by decomposing the used water absorbent resin. The solubilized product may be a product obtained by decomposing a water-swellable (i.e., water-insoluble) used water absorbent resin and solubilizing it in water. Specifically, the solubilized product includes a soluble polymer that is soluble in water and is obtained by decomposing the used water absorbent resin. Here, the soluble polymer is a polymer that is generated by breaking bonds and / or crosslinks between monomers of a water-swellable, water-insoluble polymer that is the used water absorbent resin. In addition, since water is usually also supplied to the decomposition step described later, the solubilized material is usually obtained in the form of an aqueous solution. Here, the solubilized material may be entirely solubilized in water, or may be a partially solubilized material containing a polymer that is not partially solubilized. In the aqueous solution of the solubilized material obtained in the decomposition step described later, if no undissolved residue is visible in the water and the used water absorbent resin appears dissolved in water, the used water absorbent resin is deemed to have been decomposed into the solubilized material solubilized in water. Here, the mixture supplied to the decomposition step is usually in a swollen state. Even if a part of the mixture in a swollen state remains as an undissolved swollen material after the decomposition step, if the amount of the swollen material is reduced compared to before the decomposition step, at least a part of the used water absorbent resin is decomposed. For this reason, the aqueous solution of the solubilized material that can be generated in the decomposition step is called an aqueous solution (or dispersion) of the absorbent solubilized material, even if a part of the swollen material remains as an undissolved swollen material. The solubilized adsorbed material obtained may be used as it is in the form of an aqueous solution, or may be used after drying to form a solid.
[0024] The masses of the water absorbent resin and the used water absorbent resin are numerical values converted into solid content unless otherwise specified. When the mass of the used water absorbent resin contained in the used absorbent article is unknown, the mass of the water absorbent resin can be calculated using the mass of the water absorbent resin contained in the unused absorbent article and the general value of the water absorption ratio of the used water absorbent resin. In addition, when the used absorbent article is a used disposable diaper in which the content of the used water absorbent resin is unknown, the content of the used water absorbent resin (solid content equivalent value) with respect to the total mass of the used disposable diaper can be calculated by assuming that it is 3 mass% or more and 9 mass% or less. Furthermore, depending on the mass of the used water absorbent resin, the suitable conditions for obtaining (recovering) the used water absorbent resin from the absorbent article can be appropriately adjusted. On the other hand, the actual content of the used water absorbent resin in the used absorbent article may be significantly different from the mass calculated by the above-mentioned method depending on the usage state of the used absorbent article. However, even in that case, a person skilled in the art can appropriately adjust suitable conditions for obtaining (recovering) a used water-absorbent resin from a used absorbent article while checking the actual decomposition state.
[0025] [2-5. Recycled water-absorbent resin] In one embodiment of the present invention, the "recycled water absorbent resin" is a water absorbent resin that uses the used water absorbent resin and / or its solubilized product as at least a part of the raw material. The recycled water absorbent resin may be, for example, a water absorbent resin (hereinafter, also referred to as "recycled water absorbent resin A") obtained by using the used water absorbent resin as a raw material and subjecting the used water absorbent resin to a process for discharging the absorbed liquid, such as a washing process and a dehydration process, which will be described later.
[0026] The recycled water absorbent resin may be a water absorbent resin (hereinafter, also referred to as "recycled water absorbent resin B") manufactured by using a decomposition product obtained by decomposing a used water absorbent resin as at least a part of a raw material. Here, the decomposition product includes a solubilized product of the used water absorbent resin, and optionally includes the used water absorbent resin that has not been completely decomposed until it is solubilized. In addition, in preparing the decomposition product, a process for discharging the absorbed liquid may be performed before the used water absorbent resin is decomposed, and the absorbed liquid may be discharged from the used water absorbent resin. Specific examples of the recycled water absorbent resin B include water absorbent resins manufactured by the methods shown in the following (a) to (d). (a) A method for newly producing a water absorbent resin (producing a conventional water absorbent resin using a monomer constituting the water absorbent resin as a raw material), comprising using the decomposition product as at least a part of a raw material in any one of a monomer aqueous solution preparation step, a polymerization step, a gel crushing step, a drying step, and a surface crosslinking step. (b) A method in which, in the above-mentioned method for newly producing a water absorbent resin, a step of adjusting a water absorbent resin decomposition product aqueous solution by using the water absorbent resin decomposition product instead of a monomer such as acrylic acid (salt) in the step of preparing the monomer aqueous solution is carried out instead of a step of preparing a monomer aqueous solution, and the aqueous solution of the water absorbent resin decomposition product is used instead of the monomer aqueous solution. (c) A method in which the decomposition product is crosslinked with a crosslinking agent (such as an internal crosslinking agent or a surface crosslinking agent described later) to form a crosslinked polymer, and then, in any of the above-mentioned steps, the crosslinked polymer is mixed with a newly produced water absorbent resin. (d) A method of crosslinking the decomposition product with a crosslinking agent to obtain a crosslinked polymer, and then carrying out steps similar to those of drying, pulverization, classification, surface treatment, cooling, granulation, etc. in a conventional method for newly producing a water absorbent resin.
[0027] The recycled water absorbent resin preferably has a 16-hour water soluble content of 30% by mass, more preferably 20% by mass or less, and even more preferably 10% by mass or less. The 16-hour water soluble content means the ratio (mass%) of the mass of the recycled water absorbent resin dissolved in physiological saline when the recycled water absorbent resin is immersed in physiological saline for 16 hours to the mass of the entire recycled water absorbent resin. The method for measuring the 16-hour water soluble content is not particularly limited, and a known method can be adopted, for example, the method described in the Examples can be adopted.
[0028] [2-6. Adsorbent particles] In one embodiment of the present invention, the "adsorbent particles" are not particularly limited as long as they are particles capable of adsorbing odorous components derived from the sewage components remaining in the recycled water absorbent resin, and may be, for example, one or more selected from the group consisting of activated carbon particles, silica gel, zeolite, molecular sieves, and synthetic adsorbents. When the adsorbent particles are colored particles, the color of the entire recycled water absorbent resin composition of the present invention can be changed to the color of the adsorbent particles. As a result, for example, the color of the recycled water absorbent resin composition, which is deteriorated due to the recycled water absorbent resin that has yellowed and deteriorated in color, can be improved. For this reason, specifically, the adsorbent particles are preferably one or more selected from the group consisting of activated carbon particles and synthetic adsorbents. In one embodiment of the present invention, "adsorbing odorous components derived from the sewage components, etc." means adsorbing at least one component of the odorous components derived from the sewage components, etc.
[0029] The BET specific surface area of the adsorbent particles is 200 m 2 / g or more, and 2 / g or more is more preferable, and 1000m 2 The BET specific surface area of the adsorbent particles is preferably 5000 m 2 / g or less, and 2 / g or less is more preferable, and 3000m 2 / g or less. When the BET specific surface area of the adsorbent particles is within the above range, the adsorbent particles can efficiently adsorb odorous components derived from the sewage components and the like. The method for measuring the BET specific surface area is not particularly limited, and can be measured, for example, using a specific surface area measuring device. More specifically, the BET specific surface area can be measured by the method described in the examples of the present application.
[0030] It is preferable that the adsorbent particles contain an antibacterial metal, since it can impart an antibacterial effect to the adsorbent particles and the water absorbent resin composition containing the adsorbent particles. The antibacterial metal is not particularly limited as long as it is a metal having an antibacterial effect, and examples thereof include silver, zinc, copper, and the like. The content of the antibacterial metal is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.1% by mass or more, based on the total mass of the adsorbent particles. When the content of the antibacterial metal is 0.001% by mass or more, the antibacterial effect can be suitably imparted to the adsorbent particles and the water absorbent resin composition containing the adsorbent particles. In addition, the content of the antibacterial metal is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less, based on the total mass of the adsorbent particles. By the content of the antibacterial metal being 10% by mass or less, it is possible to reduce the possibility that the adsorption performance of the adsorbent particles is reduced.
[0031] [2-7. Composition of recycled water-absorbent resin composition] In the recycled water absorbent resin composition of the present invention, the content of the recycled water absorbent resin is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, based on the mass of the entire recycled water absorbent resin composition. When the content of the recycled water absorbent resin is 1% by mass or more, the recycled water absorbent resin composition of the present invention can have a suitable water absorption performance. In addition, the content of the recycled water absorbent resin is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less, based on the mass of the entire recycled water absorbent resin composition. When the content of the recycled water absorbent resin is 60% by mass or less, the amount of odorous components and coloring components derived from the sewage components and the like remaining in the recycled water absorbent resin composition is small, and the odorous components and coloring components are suitably adsorbed to the adsorbent particles. As a result, in the recycled water absorbent resin composition of the present invention, odor generation, deterioration of color, and deterioration of water absorption performance are more unlikely to occur, and deterioration of urine resistance and increase in the amount of water-soluble components are also more unlikely to occur.
[0032] In the recycled water absorbent resin composition of the present invention, the content of the adsorbent particles is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.1% by mass or more, based on the mass of the entire recycled water absorbent resin composition. By the content of the adsorbent particles being 0.001% by mass or more, odorous components and coloring components derived from the sewage components and the like remaining in the recycled water absorbent resin composition are suitably adsorbed by the adsorbent particles. As a result, in the recycled water absorbent resin composition of the present invention, odor generation, deterioration of color and deterioration of water absorption performance are more unlikely to occur, and deterioration of urine resistance and increase in the amount of water soluble components are also more unlikely to occur. In addition, the content of the adsorbent particles is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less, based on the mass of the entire recycled water absorbent resin composition. By the content of the adsorbent particles being 10% by mass or less, the recycled water absorbent resin composition can have suitable water absorption performance.
[0033] The recycled water absorbent resin composition of the present invention may contain additives other than the recycled water absorbent resin and the adsorbent particles. The additives are not particularly limited, and examples thereof include chelating agents, reducing agents, and inorganic fine particles. The additives may be one type or a mixture of two or more types of additives. Thus, the recycled water absorbent resin composition of the present invention may contain a chelating agent and / or a reducing agent and / or inorganic fine particles. The content of the additives is not particularly limited as long as it does not impair the effect of the recycled water absorbent resin composition of the present invention.
[0034] The chelating agent is not particularly limited, and examples thereof include hydroxy polycarboxylic acid, amino polycarboxylic acid, organic polyphosphate, inorganic polyphosphate, amino polyphosphate, and tropolone derivatives, and one or more of these may be used. The content of the chelating agent is preferably 0.001% by mass or more and 5% by mass or less, more preferably 0.02% by mass or more and 1% by mass or less, and even more preferably 0.07% by mass or more and 0.5% by mass or less, based on the total mass of the recycled water absorbent resin composition. The recycled water absorbent resin composition of the present invention is preferable because the urine resistance is improved by containing the chelating agent in the above-mentioned range.
[0035] The reducing agent is not particularly limited, and examples thereof include inorganic reducing agents such as sodium sulfite, potassium sulfite, calcium sulfite, ammonium sulfite, sulfurous acid, sodium hydrogen sulfite, potassium hydrogen sulfite, ammonium hydrogen sulfite, sodium thiosulfate, potassium thiosulfate, ammonium thiosulfate, and magnesium thiosulfate, and organic reducing agents such as 2-hydroxy-2-sulfinatoacetic acid, 2-hydroxy-2-sulfonatoacetic acid, cysteine, and cystine, and one or more of these may be used. The content of the reducing agent is preferably 0.05% by mass or more and 10% by mass or less, and more preferably 0.1% by mass or more and 8% by mass or less, based on the total mass of the recycled water absorbent resin composition. The recycled water absorbent resin composition of the present invention is preferable because the reduction agent is contained in the above-mentioned range, thereby suppressing deterioration of color and deterioration of water absorption performance.
[0036] The inorganic fine particles are not particularly limited, and examples thereof include silicon dioxide and silica gel, and one or more of these may be used. The content of the inorganic fine particles is preferably 0.001% by mass to 10% by mass, more preferably 0.01% by mass to 8% by mass, and even more preferably 0.1% by mass to 5% by mass, based on the total mass of the recycled water absorbent resin composition. The recycled water absorbent resin composition of the present invention is preferable because it contains the inorganic fine particles in the above-mentioned range, thereby improving the anti-caking performance under moisture absorption.
[0037] 3. Method for producing recycled water-absorbent resin composition of the present invention A method for producing a recycled water absorbent resin composition according to one embodiment of the present invention (hereinafter referred to as "a method for producing a recycled water absorbent resin composition of the present invention") is a method for producing a recycled water absorbent resin composition of the present invention, and includes a mixing step of mixing the recycled water absorbent resin with the adsorbent particles.
[0038] The method for producing a recycled water absorbent resin composition of the present invention has an effect of producing the recycled water absorbent resin composition of the present invention, i.e., a recycled water absorbent resin composition which is less likely to cause odor generation, deterioration in color and deterioration in water absorption performance, and which is also less likely to cause deterioration in urine resistance and increase in the amount of water-soluble components.
[0039] Each step constituting the method for producing the water-absorbing resin composition of the present invention will be described below. In the method for producing the water-absorbing resin composition of the present invention, the above description is applied to the members constituting the water-absorbing resin composition of the present invention.
[0040] [3-1. Mixing process] In the method for producing a water absorbent resin composition of the present invention, the "mixing step" is a step of mixing the recycled water absorbent resin with the adsorbent particles. In the method for producing a water absorbent resin composition of the present invention, "mixing the recycled water absorbent resin with the adsorbent particles" may be a step of mixing the recycled water absorbent resin A or recycled water absorbent resin B prepared in the preparation step of recycled water absorbent resin A or the preparation step of recycled water absorbent resin B described below with the adsorbent particles. In addition, the mixing step may be a step of providing (adding) the adsorbent particles in a step during the preparation step of recycled water absorbent resin A or the preparation step of recycled water absorbent resin B in order to finally produce a recycled water absorbent resin composition containing the recycled water absorbent resin and the adsorbent particles.
[0041] [3-2. Preparation process of recycled water absorbent resin A] In the method for producing the water absorbent resin composition of the present invention, when a recycled water absorbent resin A is used as the recycled water absorbent resin, the method may include a step of preparing the recycled water absorbent resin A. The step of preparing the recycled water absorbent resin A may be, for example, the following step (i) or (ii).
[0042] (i) A process of obtaining a used water absorbent resin separated from a used absorbent article, and then performing a process of discharging the absorbed liquid from the used water absorbent resin, thereby preparing a "recycled water absorbent resin A".
[0043] (ii) A process for separating a used water absorbent resin from a used absorbent article, and then performing a process for discharging the absorbed liquid from the used water absorbent resin, thereby preparing a "recycled water absorbent resin A".
[0044] After carrying out the preparation step of the recycled water absorbent resin A, the prepared recycled water absorbent resin A is subjected to the mixing step, and the mixing step is carried out, whereby the water absorbent resin composition of the present invention can be produced.
[0045] In addition, in the case where a recycled water absorbent resin A is used as the recycled water absorbent resin, the method for producing a water absorbent resin composition of the present invention can also produce the water absorbent resin composition of the present invention by separately obtaining the recycled water absorbent resin A, subjecting the obtained recycled water absorbent resin A to the mixing step, and carrying out the mixing step, instead of carrying out the preparation step of the recycled water absorbent resin A.
[0046] In the case where the recycled water absorbent resin A is prepared in the steps (i) and (ii), the method for producing the water absorbent resin composition of the present invention may include, for example, a washing step described later and / or a dehydration step described later as a step for discharging the absorbed liquid. In addition, in the case where the recycled water absorbent resin A is prepared in the step (ii), the method for producing the water absorbent resin composition of the present invention may include a separation step described later.
[0047] <Cleaning process> The washing step is specifically a step of removing the absorbed liquid from the used water absorbent resin with washing water. Here, the used water absorbent resin has absorbed the absorbed liquid and is in a swollen water absorbent resin gel (swollen gel) state. Specific methods include, for example, pouring washing water onto the swollen gel, immersing the swollen gel in washing water, and stirring the swollen gel while immersing it in washing water.
[0048] The washing water is not particularly limited as long as it can reduce the amount of absorbed liquid in the used water absorbent resin compared to before the treatment by the washing step and does not cause the water absorbent resin to change in quality. The washing water is preferably one that allows the used water absorbent resin to absorb and swell. This is because the absorbed liquid is easily removed when dehydrating after the resin absorbs and swells. Examples of such aqueous liquids that can be used include deionized water, tap water, distilled water, saline, and seawater. The aqueous liquid may also contain other components.
[0049] The cleaning water may be hot, ranging from room temperature to 100° C., or may be steam. When a hot aqueous liquid or a steam aqueous liquid is used as the cleaning water, not only a cleaning effect but also a sterilizing effect can be expected.
[0050] <Dehydration process> The dehydration step is a step of discharging the absorbed liquid from the used water absorbent resin. The used water absorbent resin separated from the used absorbent article to be subjected to the dehydration step is not particularly limited as long as it is a water absorbent resin separated from the used absorbent article. The water absorbent resin separated from the used absorbent article to be subjected to the dehydration step may include, for example, a used water absorbent resin and a water absorbent resin after being washed in the washing step. The water absorbent resin to be subjected to the dehydration step is usually in a swollen gel state.
[0051] The dehydration step is, in detail, a step of discharging the absorbed liquid present inside the used water-absorbent resin to the outside of the absorbent resin by shrinking the swollen gel. The absorbed liquid may contain, for example, water-soluble components and human waste components. In addition, when the washing step is performed before the dehydration step, the washing water used in the washing step may also be included in the absorbed liquid.
[0052] The treatment method in the dehydration step is not particularly limited as long as it is a treatment capable of reducing the moisture content of the swollen water absorbent resin. The dehydration step may include contacting the used water absorbent resin separated from the used absorbent article with one or more selected from the group consisting of a polyvalent metal salt, an aqueous solution containing a polyvalent metal salt, an acidic liquid, a hydrophilic organic solvent, and an aqueous solution containing a hydrophilic organic solvent. Hereinafter, the one selected from the group consisting of a polyvalent metal salt, an aqueous solution containing a polyvalent metal salt, an acidic liquid, a hydrophilic organic solvent, and an aqueous solution containing a hydrophilic organic solvent that can be used in the dehydration step is also referred to as a "dehydration chemical". More specifically, the dehydration step may be carried out, for example, by a method of contacting a swollen gel of a water absorbent resin with an aqueous solution containing a hydrophilic organic solvent; a method of contacting the swollen gel with an aqueous solution of a low pH (e.g., 3 or less); a method of contacting the swollen gel with an aqueous solution of a polyvalent metal salt such as calcium chloride, or the like. Specific examples of contacting the swollen gel of the water-absorbent resin with these liquids include pouring the liquid onto the swollen gel, immersing the swollen gel in the liquid, stirring the swollen gel while immersing it in the liquid, etc. The dehydration step can also be carried out by a method of applying a voltage to the swollen gel using a pair of electrodes.
[0053] In the case where a swollen gel of a water absorbent resin is immersed in an aqueous solution containing a hydrophilic organic solvent, the concentration of the hydrophilic organic solvent in the aqueous solution to be immersed is preferably 35% by mass or more, more preferably 40% by mass or more, and further preferably 45% by mass or more.
[0054] The hydrophilic organic solvent is an organic solvent having a solubility of 20 g or more in 100 mL of water at 20° C. More preferably, the solubility is 25 g or more in 100 mL of water at 20° C., and even more preferably, the solubility is 30 g or more in 100 mL of water at 20° C.
[0055] Examples of such hydrophilic organic solvents include (1) lower alcohols, such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, tert-butyl alcohol, etc., (2) ketones, such as acetone, methyl ethyl ketone, etc., (3) ethers, such as tetrahydrofuran, dioxane, etc., and (4) esters, such as methyl acetate, methyl lactate, ethyl lactate, etc. These hydrophilic organic solvents may be used alone or in combination of two or more kinds.
[0056] When the swollen gel of the water-absorbent resin is immersed in an aqueous solution with a low pH (for example, 3 or less), the pH of the aqueous solution is preferably 3 or less, and more preferably 0.5 to 2.5. In the aqueous solution, either an inorganic acid or an organic acid can be used as the acid. In the case of an inorganic acid, hydrochloric acid, sulfuric acid, etc. can be used. In the case of an organic acid, tartaric acid, glycolic acid, malic acid, citric acid, succinic acid, acetic acid, etc. can be used. These acids may be used alone or in combination of two or more.
[0057] In the case of contacting with an aqueous solution of a polyvalent metal salt, examples of the polyvalent metal salt include metal salts of calcium, magnesium, aluminum, iron, cobalt, nickel, and copper. These polyvalent metal salts may be used alone or in combination of two or more.
[0058] In the preparation process of the recycled water absorbent resin A, only one of the washing step and the dehydration step may be performed, or both of the washing step and the dehydration step may be performed. When the preparation process of the recycled water absorbent resin A includes both the washing step and the dehydration step, the order of performing each step is not limited. In addition, each of the washing step and the dehydration step may be performed multiple times. Specifically, for example, the preparation process of the recycled water absorbent resin A may include performing the washing step on the used water absorbent resin separated from the used absorbent article, and then performing the dehydration step to prepare the recycled water absorbent resin. This is because the water absorbent resin absorbs the washing water and further swells in the washing step, and when the absorbed liquid is discharged in the subsequent dehydration step, a larger amount of absorbed liquid can be discharged compared to the case of simply performing the dehydration step.
[0059] In addition, when the discharged absorbed liquid adheres to the surface of the water absorbent resin again, the washing step, the dehydration step, and the washing step are performed in this order, so that the absorbed liquid that adheres to the surface of the water absorbent resin after the dehydration step can be washed away, which is a more preferable method. The preparation step of the recycled water absorbent resin A may also include preparing the recycled water absorbent resin A by performing the washing step, the dehydration treatment step, the washing step, and the dehydration treatment step in this order on the used water absorbent resin separated from the used absorbent article.
[0060] <Separation process> The separation step specifically refers to removing the used water absorbent resin from gaps in the pulp, nonwoven fabric, etc. contained in the used absorbent article and dispersing it in the treatment liquid. The method for carrying out the separation step is not particularly limited as long as the used water absorbent resin can be separated from the used absorbent article, and known methods can be applied. As a method for carrying out the separation step, for example, a method of stirring a mixture of the treatment liquid and the used absorbent article can be mentioned. The water absorbent resin dispersed in the treatment liquid can be recovered by a conventional solid-liquid separation means for separating soluble and insoluble substances, for example, filtration, centrifugation, etc.
[0061] The treatment liquid is not particularly limited, and for example, a liquid corresponding to the cleaning liquid or the dehydration chemical can be used. Here, when the cleaning liquid is used as the treatment liquid, the separation step and the washing step can be performed in parallel. In that case, the used water absorbent resin is dispersed in the treatment liquid, i.e., the washing liquid, and then washed. Thereafter, the washed water absorbent resin can be recovered from the treatment liquid by the solid-liquid separation means. Furthermore, when a liquid corresponding to the dehydration chemical is used as the treatment liquid, the separation step and the dehydration step can be performed in parallel. In that case, the used water absorbent resin is dispersed in the treatment liquid, i.e., the liquid corresponding to the dehydration chemical, and then dehydrated. Thereafter, the dehydrated water absorbent resin can be recovered from the treatment liquid by the solid-liquid separation means.
[0062] <Drying process, crushing / classification process> The preparation process of the recycled water absorbent resin A may include carrying out a drying process described below and / or a pulverization and classification process described below. When carrying out the drying process and the pulverization process, the order is not limited, and the pulverization process may be carried out after the drying process, or conversely, the drying process may be carried out after the pulverization process. In addition, each of the drying process and the pulverization process may be carried out multiple times. For example, in the preparation process of the recycled water absorbent resin A, after carrying out the drying process, the water absorbent resin dried in the drying process may be pulverized in the pulverization process, and then the water absorbent resin pulverized and classified in the pulverization and classification process may be dried again by carrying out the drying process.
[0063] The drying step is a step of drying the water absorbent resin to reduce its moisture content. The water absorbent resin to be subjected to the drying step is not particularly limited as long as it is a water absorbent resin separated from a used absorbent article. The water absorbent resin to be subjected to the washing step may include, for example, a used water absorbent resin, a water absorbent resin after being treated in the washing step and / or the dehydration treatment step, and a water absorbent resin after being pulverized in a pulverization step described below.
[0064] By carrying out the drying step, the resin solid content of the recycled water absorbent resin A to be prepared can be controlled within a desired range. The resin solid content can be calculated from the loss on drying (the change in mass when 1 g of the water absorbent resin is heated at 180°C for 3 hours). The resin solid content is, for example, preferably 80% by mass or more, more preferably 85% by mass or more and 99% by mass or less, even more preferably 90% by mass or more and 98% by mass or less, and particularly preferably 92% by mass or more and 97% by mass or less.
[0065] In the drying step, the method for drying the water-absorbent resin is not particularly limited, and a known drying method can be applied. Examples of the method for drying the water-absorbent resin include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, and high humidity drying using high-temperature water vapor. Among the above-mentioned drying methods, hot air drying is preferred from the viewpoint of drying efficiency, and band drying in which hot air drying is performed on a ventilation belt is more preferred. In addition, for example, heat drying using an oven can be applied as a method for drying the water-absorbent resin.
[0066] The drying temperature (temperature of hot air) in the hot air drying is preferably 120°C or higher and 250°C or lower, more preferably 150°C or higher and 200°C or lower, from the viewpoint of the color of the water absorbent resin, drying efficiency, etc. In addition, the drying conditions other than the drying temperature, such as the wind speed of the hot air and the drying time, may be appropriately set according to the moisture content, total mass, and target resin solid content of the water absorbent resin to be dried. When band drying is performed, the various conditions described in International Publication Nos. 2006 / 100300, 2011 / 025012, 2011 / 025013, 2011 / 111657, etc. are appropriately applied as drying conditions.
[0067] By setting the above-mentioned drying temperature, drying time, etc. within the above-mentioned ranges, it is possible to set the CRC (absorption capacity), Ext (amount of 16-hour water-soluble component) and color within desired ranges in the recovered water absorbent resin and the reusable water absorbent resin in the manufacturing method for the recycled water absorbent resin of the present invention.
[0068] <Crushing / classification process> The drying step in the preparation step of the recycled water absorbent resin A is a step of pulverizing and classifying the water absorbent resin to adjust its shape and size (particle diameter). The water absorbent resin to be subjected to the pulverizing and classifying step is not particularly limited as long as it is a water absorbent resin separated from a used absorbent article. The water absorbent resin to be subjected to the pulverizing and classifying step may include, for example, a used water absorbent resin, a water absorbent resin after being treated in the washing step and / or the dehydration treatment step, and a water absorbent resin after being dried in the drying step.
[0069] By carrying out the pulverization and classification process, the shape and size (particle diameter) of the recycled water absorbent resin A to be prepared can be controlled within a desired range. As a result, the shape and size (particle diameter) of the recycled water absorbent resin A can be controlled within a desired range. The particle size distribution of the recycled water absorbent resin A is preferably such that the mass median particle diameter (D50) is 300 μm or more and 600 μm or less, and the proportion of particles less than 150 μm is 5 mass% or less. The upper limit of the mass median particle diameter (D50) is more preferably 500 μm or less, further preferably 450 μm or less, and particularly preferably 400 μm or less. The proportion of particles less than 150 μm is more preferably 4 mass% or less, further preferably 3 mass% or less, and particularly preferably 2 mass% or less.
[0070] In the pulverization and classification step, the method for pulverizing the water-absorbent resin is not particularly limited, and a known pulverization method can be applied. As a method for pulverizing the water-absorbent resin, for example, a method using a vibration mill can be mentioned.
[0071] In the pulverization and classification step, the method for classifying the water-absorbent resin is not particularly limited, and a known classification method can be applied. For example, a method using a sieve with appropriate mesh size can be mentioned as a method for classifying the water-absorbent resin.
[0072] [3-3. Preparation process of recycled water absorbent resin B] In the method for producing the water absorbent resin composition of the present invention, when a recycled water absorbent resin B is used as the recycled water absorbent resin, a preparation step of the recycled water absorbent resin B may be included. The preparation step of the recycled water absorbent resin B may be, for example, a step of preparing the recycled water absorbent resin B by any of the above-mentioned methods (a) to (d). Hereinafter, each step constituting the "method for preparing the decomposition product" and the "method for newly producing a water absorbent resin", i.e., the "method for producing a conventional water absorbent resin using a monomer constituting a water absorbent resin as a raw material" in the above-mentioned (a) to (d) will be described.
[0073] [Method for preparing decomposition products] The method for preparing the decomposition product is not particularly limited as long as the decomposition product can be prepared by decomposing the water absorbent resin, and a known method can be adopted. Methods for preparing the decomposition product are described in, for example, JP 2019-131789 A (Patent Document 5), Japanese Patent No. 3146053, Japanese Patent No. 3091251, JP 2017-128840 A, JP 2019-108639 A, and JP 2019-108640 A.
[0074] Specifically, Patent Document 5 describes a method for decomposing and solubilizing a superabsorbent resin using a reducing agent and a transition metal ion. Patent No. 3146053 describes a method for decomposing and solubilizing a superabsorbent resin when the pH is 4 or more and 7.5 or less using ascorbic acid as a reducing agent. Patent No. 3091251 describes a method for decomposing and solubilizing a superabsorbent resin by heat treatment in the presence of an oxidizing agent. JP 2017-128840 A describes a method for decomposing and solubilizing a superabsorbent resin by immersing it in ozone water. JP 2019-108639 A describes a method for decomposing and solubilizing a superabsorbent resin under acidic conditions using chlorine dioxide. JP 2019-108640 A describes a method for decomposing and solubilizing a superabsorbent resin using a peracid.
[0075] [Each step constituting the method for producing a new water-absorbent resin] <Preparation of Monomer Aqueous Solution> This step is a step of preparing an aqueous solution containing acrylic acid (salt) as a main component (hereinafter referred to as "aqueous monomer solution"). Although a slurry liquid of a monomer can be used within a range in which the water absorption performance of the obtained water absorbent resin is not deteriorated, for the sake of convenience, the aqueous monomer solution will be described in this section.
[0076] The "main component" means that the amount (content) of acrylic acid (salt) used is usually 50 mol % or more, preferably 70 mol % or more, and more preferably 90 mol % or more (upper limit: 100 mol %) based on the total amount of monomers (excluding internal crosslinking agents) used in the polymerization reaction of the water absorbent resin.
[0077] (acrylic acid) In one embodiment of the present invention, from the viewpoint of the physical properties and productivity of the obtained water absorbent resin, acrylic acid and / or a salt thereof (hereinafter referred to as "acrylic acid (salt)") is used as a monomer constituting the water absorbent resin.
[0078] The "acrylic acid" may be a known acrylic acid, and may contain, as a polymerization inhibitor, preferably methoxyphenols, more preferably p-methoxyphenol, in an amount of preferably 200 ppm or less, more preferably 10 ppm or more to 160 ppm or less, and even more preferably 20 ppm or more to 100 ppm or less, from the viewpoint of the polymerizability of acrylic acid. As for impurities in acrylic acid, the compounds described in U.S. Patent Application Publication No. 2008 / 0161512 are also applicable to one embodiment of the present invention.
[0079] The "acrylate" is obtained by neutralizing the acrylic acid with the following basic composition. The acrylate may be a commercially available acrylate (e.g., sodium acrylate) or may be one obtained by neutralization in a production plant for a water absorbent resin.
[0080] (Basic Composition) In one embodiment of the present invention, the term "basic composition" refers to a composition containing a basic compound, such as a commercially available aqueous sodium hydroxide solution.
[0081] Specific examples of the basic compound include alkali metal salts such as carbonates and / or hydrogen carbonates of alkali metals, and hydroxides of alkali metals such as sodium hydroxide, potassium hydroxide, and lithium hydroxide. Other basic compounds include ammonia and organic amines. Among these, it is desirable to use a strong base from the viewpoint of the physical properties of the water absorbent resin to be obtained. That is, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred, and sodium hydroxide is more preferred.
[0082] (neutralization) As the neutralization in one embodiment of the present invention, either neutralization of acrylic acid (before polymerization) or neutralization of a hydrogel-like crosslinked polymer obtained by crosslinking and polymerizing acrylic acid (after polymerization) (hereinafter referred to as "post-neutralization") can be selected or used in combination. When the solubilized polymer of the present invention is used as a raw material (recycled raw material) for the production of a water-absorbent resin, if the solubilized polymer contains a basic compound, this basic compound neutralizes the acrylic acid before polymerization or the hydrogel-like crosslinked polymer after polymerization. Therefore, as described later, the neutralization rate of the water-absorbent resin as a final product is adjusted to a predetermined range by adding this basic compound. In addition, these neutralizations may be continuous or batch-wise and are not particularly limited, but a continuous type is preferable from the viewpoint of production efficiency and the like.
[0083] Regarding the conditions such as the neutralization apparatus, neutralization temperature, and residence time, the conditions described in International Publication No. 2009 / 123197 and US Patent Application Publication No. 2008 / 0194863 are also applied to the present invention.
[0084] In one embodiment of the present invention, the neutralization rate is preferably 10 mol% to 90 mol%, more preferably 40 mol% to 85 mol%, even more preferably 50 mol% to 80 mol%, and particularly preferably 60 mol% to 75 mol% based on the acid group of the monomer. If the neutralization rate is less than 10 mol%, the water absorption capacity may be significantly reduced. On the other hand, if the neutralization rate exceeds 90 mol%, a water absorbent resin with a high water absorption capacity under pressure may not be obtained. Note that a neutralization rate of 75 mol% means a mixture of 25 mol% acrylic acid and 75 mol% acrylic acid salt. The mixture may also be called a partially neutralized product of acrylic acid.
[0085] The neutralization rate is the same in the case of post-neutralization. The neutralization rate is also applied to the neutralization rate of the water-absorbent resin as a final product. The present invention is characterized in that the solubilized polymer is used as a part of the raw material in the production of the water-absorbent resin. When the solubilized polymer contains a basic compound, the neutralization of the acrylic acid (before polymerization) and / or the post-neutralization of the hydrogel crosslinked polymer are appropriately adjusted so that the neutralization rate of the water-absorbent resin as a final product, including the basic compound, falls within a predetermined range.
[0086] (Other monomers) In one embodiment of the present invention, the term "other monomer" refers to a monomer other than the acrylic acid (salt), and the water-absorbing resin can be produced by using the other monomer together with the acrylic acid (salt).
[0087] The other monomer may be a water-soluble or hydrophobic unsaturated monomer. Specifically, the compounds described in U.S. Patent Application Publication No. 2005 / 0215734 (excluding acrylic acid) are also applicable to one embodiment of the present invention.
[0088] (Internal crosslinking agent) As the internal crosslinking agent used in one embodiment of the present invention, the compounds described in U.S. Patent No. 6,241,928 are also applied to one embodiment of the present invention. Among these, one or more compounds are selected in consideration of reactivity.
[0089] In addition, from the viewpoint of the water absorption performance of the obtained water absorbent resin, preferably a compound having two or more polymerizable unsaturated groups, more preferably a compound having thermal decomposition properties at the drying temperature described below, and even more preferably a compound having two or more polymerizable unsaturated groups having a (poly)alkylene glycol structural unit, is used as the internal crosslinking agent.
[0090] The polymerizable unsaturated group is preferably an allyl group or a (meth)acrylate group, more preferably a (meth)acrylate group. The (poly)alkylene glycol structural unit is preferably polyethylene glycol, and the number n is preferably 1 or more and 100 or less, more preferably 6 or more and 50 or less.
[0091] The amount of the internal crosslinking agent used is preferably 0.0001 mol% or more and 10 mol% or less, more preferably 0.001 mol% or more and 1 mol% or less, based on the total amount of monomers. By setting the amount used within the above range, a desired water-absorbing resin can be obtained. If the amount used is too small, the gel strength tends to decrease and the amount of water-soluble components tends to increase, and if the amount used is too large, the water absorption capacity tends to decrease, which is not preferable.
[0092] In one embodiment of the present invention, a method is preferably applied in which a predetermined amount of an internal crosslinking agent is added to an aqueous monomer solution in advance, and a crosslinking reaction is carried out simultaneously with polymerization. On the other hand, in addition to this method, a method of post-crosslinking by adding an internal crosslinking agent during and / or after polymerization, a radical crosslinking method using a radical polymerization initiator, a radiation crosslinking method using active energy rays such as electron beams and ultraviolet rays, etc. can also be adopted. These methods can also be used in combination.
[0093] (Other substances added to the monomer aqueous solution) In one embodiment of the present invention, from the viewpoint of improving the physical properties of the resulting water-absorbent resin, the following substances may be added during preparation of the aqueous monomer solution.
[0094] Specifically, hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salts), and crosslinked polyacrylic acid (salts) can be added in amounts of preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (lower limit: 0% by mass); foaming agents such as carbonates, azo compounds, and bubbles, surfactants, chelating agents, chain transfer agents, etc. can be added in amounts of preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (lower limit: 0% by mass); etc. can be added in amounts of preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (lower limit: 0% by mass).
[0095] The substance may be added not only to the aqueous monomer solution but also during the polymerization, or these forms may be used in combination.
[0096] When a water-soluble resin or a water-absorbent resin is used as the hydrophilic polymer, a graft polymer or a water-absorbent resin composition (e.g., a starch-acrylic acid polymer, a PVA-acrylic acid polymer, etc.) is obtained. These polymers and water-absorbent resin compositions are also within the scope of the present invention.
[0097] <Polymerization process> This step is a step of polymerizing the acrylic acid (salt)-based monomer aqueous solution obtained in the monomer aqueous solution preparation step to obtain a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel"). In addition, when the monomer aqueous solution contains the decomposition product, or when an aqueous solution of the decomposition product is used instead of the monomer aqueous solution, this step can also be a step of polymerizing a soluble polymer constituting the decomposition product to obtain a hydrogel.
[0098] (Polymerization initiator) The polymerization initiator used in one embodiment of the present invention is not particularly limited since it is appropriately selected depending on the polymerization form, etc. For example, a thermally decomposable polymerization initiator, a photodecomposable polymerization initiator, or a redox-based polymerization initiator in combination with a reducing agent that promotes the decomposition of these polymerization initiators can be mentioned. Specifically, one or more of the polymerization initiators disclosed in U.S. Pat. No. 7,265,190 are used. From the viewpoint of the handling of the polymerization initiator, the physical properties of the water-absorbing resin, etc., preferably a peroxide or an azo compound is used, more preferably a peroxide, and even more preferably a persulfate.
[0099] The amount of the polymerization initiator used is preferably 0.001 mol % to 1 mol %, more preferably 0.001 mol % to 0.5 mol %, based on the monomer. The amount of the reducing agent used is preferably 0.0001 mol % to 0.02 mol %, based on the monomer.
[0100] Instead of the polymerization initiator, the polymerization reaction may be carried out by irradiation with active energy rays such as radiation, electron beams, and ultraviolet rays, or these active energy rays may be used in combination with the polymerization initiator.
[0101] (polymerization form) The polymerization form applied to one embodiment of the present invention is not particularly limited, but from the viewpoint of water absorption characteristics, ease of polymerization control, etc., preferably, spray droplet polymerization, aqueous solution polymerization, and reversed phase suspension polymerization, more preferably, aqueous solution polymerization, and reversed phase suspension polymerization, and further preferably, aqueous solution polymerization are mentioned. Among them, continuous aqueous solution polymerization is particularly preferable, and either continuous belt polymerization or continuous kneader polymerization is applicable.
[0102] As specific polymerization forms, continuous belt polymerization is disclosed in U.S. Patent Nos. 4,893,999, 6,241,928, U.S. Patent Application Publication No. 2005 / 215734, etc., and continuous kneader polymerization is disclosed in U.S. Patent Nos. 6,987,151, 6,710,141, etc. By adopting these continuous aqueous solution polymerizations, the production efficiency of the water absorbent resin is improved.
[0103] In addition, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization." "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of the aqueous monomer solution of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point). "High-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination.
[0104] In one embodiment of the present invention, the polymerization can also be carried out under an air atmosphere. In the prepolymerization step, the polymerization is preferably carried out under an inert gas atmosphere such as nitrogen or argon. In this case, for example, it is preferable to control the oxygen concentration to 1% by volume or less. It is also preferable to replace the dissolved oxygen in the aqueous monomer solution with an inert gas (for example, dissolved oxygen: less than 1 mg / l). In one embodiment of the present invention, the polymerization can also be carried out as a foaming polymerization in which bubbles (particularly the inert gas, etc.) are dispersed in the aqueous monomer solution to carry out the polymerization.
[0105] <Gel crushing process> In this step, the hydrogel obtained in the polymerization step is gel-pulverized by a screw extruder such as a kneader or meat chopper, or a gel pulverizer such as a cutter mill, to obtain a particulate hydrogel (hereinafter referred to as "particulate hydrogel"). When the polymerization step is kneader polymerization, the polymerization step and the gel pulverization step are carried out simultaneously. When the particulate hydrogel is obtained directly in the polymerization process, such as in gas phase polymerization or reversed phase suspension polymerization, the gel pulverization step may not be carried out.
[0106] As for the gel crushing conditions and forms other than those described above, the contents disclosed in WO 2011 / 126079 are preferably applied to the present invention.
[0107] <Gel drying process> This step is a step of obtaining a dry polymer by drying the particulate hydrogel obtained in the polymerization step and / or gel crushing step to a desired resin solid content. The resin solid content is determined from the loss on drying (the change in mass when 1 g of the water-absorbent resin is heated at 180°C for 3 hours), and is preferably 80% by mass or more, more preferably 85% by mass to 99% by mass, even more preferably 90% by mass to 98% by mass, and particularly preferably 92% by mass to 97% by mass.
[0108] The method for drying the particulate hydrogel is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high temperature water vapor, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferred, and band drying in which hot air drying is performed on a ventilation belt is more preferred.
[0109] The drying temperature (hot air temperature) in the hot air drying is preferably 120° C. or higher and 250° C. or lower, more preferably 150° C. or higher and 200° C. or lower, from the viewpoint of drying efficiency, etc. The drying conditions other than the drying temperature, such as the hot air speed and drying time, may be appropriately set depending on the water content and total mass of the particulate hydrogel to be dried and the intended resin solid content, and when band drying is performed, the conditions described in WO 2006 / 100300, WO 2011 / 025012, WO 2011 / 025013, WO 2011 / 111657, etc. are appropriately applied.
[0110] By setting the above-mentioned drying temperature, drying time, etc. within the above-mentioned ranges, the CRC (absorbency ratio), Ext (amount of water-soluble component), etc. of the obtained water-absorbent resin can be set within the below-mentioned suitable ranges.
[0111] <Crushing process and classification process> This step is a step in which the dried polymer obtained through the gel drying step is pulverized (pulverization step), and fine powder is removed from the pulverized dried polymer (classification step) to obtain a water-absorbent resin precursor.
[0112] The apparatus used in the pulverization step is not particularly limited, but includes high-speed rotary pulverizers such as roll mills, hammer mills, screw mills, and pin mills; knuckle-type pulverizers; cylindrical mixers, etc. Among them, roll mills are preferred from the viewpoint of pulverization efficiency. A plurality of these pulverizers can also be used in combination.
[0113] The particle size adjustment method in the classification step includes sieve classification using a JIS standard sieve (JIS Z 8801-1 (2000)) and air flow classification. Among them, sieve classification is preferred from the viewpoint of classification efficiency. Note that, from the viewpoint of ease of pulverization, classification may be additionally performed before the pulverization step.
[0114] <Surface crosslinking process> This step is a step of providing a portion with a higher crosslink density on the surface layer (a portion several tens of μm from the surface of the water absorbent resin precursor) of the water absorbent resin precursor obtained through the above-mentioned steps, and is composed of a mixing step, a heat treatment step, and a cooling step (optional).
[0115] In the surface cross-linking step, a surface-cross-linked water-absorbent resin is obtained by radical cross-linking, surface polymerization, cross-linking reaction with a surface cross-linking agent, or the like on the surface of the water-absorbent resin precursor.
[0116] (Surface cross-linking agent) The surface cross-linking agent used in one embodiment of the present invention is not particularly limited, but may be an organic or inorganic surface cross-linking agent. Among them, from the viewpoint of the physical properties of the water-absorbent resin, the handling property of the surface cross-linking agent, etc., an organic surface cross-linking agent that reacts with a carboxyl group is preferred. For example, one or more surface cross-linking agents disclosed in U.S. Patent No. 7,183,456 may be mentioned. More specifically, polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyamine compounds or their condensates with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal salts, alkylene carbonate compounds, cyclic urea compounds, etc. may be mentioned.
[0117] The amount of the surface crosslinking agent used (when a plurality of agents are used, the total amount used) is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the water-absorbent resin precursor. The surface crosslinking agent is preferably added as an aqueous solution, and in this case, the amount of water used is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the water-absorbent resin precursor. Furthermore, when a hydrophilic organic solvent is used as necessary, the amount used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the water-absorbent resin precursor.
[0118] In addition, each of the additives added in the "re-moistening step" described later can be added by mixing it with the surface crosslinking agent (aqueous solution) in a range of 5 parts by mass or less, or can be added separately in this mixing step.
[0119] (Mixing process) This step is a step of mixing the water-absorbent resin precursor and the surface crosslinking agent. The method of mixing the surface crosslinking agent is not particularly limited, but includes a method of preparing a surface crosslinking agent solution in advance, and preferably spraying or dropping the liquid onto the water-absorbent resin precursor, more preferably spraying and mixing. The device for performing the mixing is not particularly limited, but preferably includes a high-speed stirring mixer, more preferably a high-speed stirring continuous mixer.
[0120] (Heat treatment process) This step is a step of applying heat to the mixture discharged from the mixing step to cause a crosslinking reaction on the surface of the water-absorbent resin precursor. The device for carrying out the crosslinking reaction is not particularly limited, but a paddle dryer is preferred. The reaction temperature in the crosslinking reaction is appropriately set according to the type of surface crosslinking agent used, and is preferably 50°C or higher and 300°C or lower, more preferably 100°C or higher and 200°C or lower.
[0121] (cooling process) This step is an optional step that is installed as necessary after the heat treatment step. The cooling device is not particularly limited, but is preferably a device with the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. The surface-crosslinked water-absorbent resin obtained in the heat treatment step is forcibly cooled, as necessary, in the cooling step, preferably to 40°C or more and 80°C or less, more preferably to 50°C or more and 70°C or less.
[0122] <Mode and timing of adding decomposition product> Examples of methods for adding (providing) the decomposition product include adding it as an aqueous solution, adding it as a powder after drying it, and adding it as an aqueous dispersion (slurry) with some undissolved material remaining.
[0123] When the decomposition product is added in the "process for preparing an aqueous monomer solution", the water absorbent resin decomposition product (or its aqueous solution and / or aqueous dispersion) may be mixed with the aqueous monomer solution, or the decomposition product (or its aqueous solution and / or aqueous dispersion) may be mixed with water in advance and then the monomer (or its aqueous solution) may be mixed. From the viewpoint of uniform mixing of the raw materials, it is preferable to mix the decomposition product (or its aqueous solution and / or aqueous dispersion) with the aqueous monomer solution. The decomposition product and / or the aqueous solution of the decomposition product and / or the aqueous dispersion of the decomposition product may be heated to 50° C. or higher before being added.
[0124] When the decomposition product is added in the "polymerization step", the decomposition product (or its aqueous solution and / or aqueous dispersion) may be added before or after the start of polymerization. From the viewpoint of uniformity of the polymer component, it is preferable to add the decomposition product (or its aqueous solution and / or aqueous dispersion) before the start of polymerization.
[0125] When the decomposition product is added in the "gel crushing step", the decomposition product (or its aqueous solution and / or aqueous dispersion) may be added before crushing or during crushing. It may also be added in portions. From the viewpoint of uniformity of the gel component, it is preferable to add the decomposition product (or its aqueous solution and / or aqueous dispersion) before gel crushing.
[0126] When the decomposition product is added in the "gel drying step", the hydrogel and the decomposition product (or an aqueous solution and / or aqueous dispersion thereof) may be mixed before drying.
[0127] When the decomposition product is added in the "surface cross-linking step", the decomposition product (or its aqueous solution and / or aqueous dispersion) may be mixed with a water absorbent resin that has been dried in advance. From the viewpoint of uniform mixing of the surface treatment liquid and the water absorbent resin, it is preferable to use the decomposition product in a powder form and handle the entire product in a powder form.
[0128] When the step of preparing the recycled water absorbent resin B includes the gel drying step, it is preferable to provide (add) the decomposition product as at least a part of the raw material of the recycled water absorbent resin by the end of the gel drying step. As described above, the decomposition product is the used water absorbent resin and / or its solubilized product. By providing the decomposition product by the end of the gel drying step, the water content (resin solid content) of the recycled water absorbent resin B and the recycled water absorbent resin composition prepared can be suitably controlled by controlling the drying conditions of the gel drying step.
[0129] [3-4. Timing of mixing process] The timing of carrying out the mixing step is not particularly limited as long as the recycled water absorbent resin composition containing the recycled water absorbent resin and the adsorbent particles can be finally produced. For example, when the method for producing the water absorbent resin composition of the present invention includes a preparation step of the recycled water absorbent resin A, and the preparation step of the recycled water absorbent resin A includes a step of discharging the absorbed liquid, it is preferable that the mixing step is carried out after carrying out the step of discharging the absorbed liquid. In that case, it is possible to avoid discharging the adsorbent particles provided together with the absorbed liquid, and finally produce a recycled water absorbent resin composition in which the recycled water absorbent resin A and the adsorbent particles are suitably mixed.
[0130] In addition, when the method for producing a water absorbent resin composition of the present invention includes a preparation step of a recycled water absorbent resin B, and the step of preparing the recycled water absorbent resin B includes the gel drying step, it is preferable to carry out the mixing step after the gel drying step. Furthermore, it is more preferable to provide the used water absorbent resin and / or its solubilized product as at least a part of the raw material of the recycled water absorbent resin before the gel drying step is completed, and to carry out the mixing step after the gel drying step. By carrying out the mixing step after the gel drying step, the recycled water absorbent resin B or its precursor (water absorbent resin precursor) and the adsorbent particles can be mixed more uniformly in the mixing step. As a result, a recycled water absorbent resin composition in which the recycled water absorbent resin B and the adsorbent particles are mixed more uniformly can be finally produced.
[0131] 3-5. Water absorption performance of recycled water absorbent resin and recycled water absorbent resin composition The water absorption properties of the water absorbent resin may be CRC of 25 g / g or more, 27 g / g or more, or 30 g / g or more, and AAP (0.3 psi) of 10 g / g or more, 15 g / g or more, 20 g / g or more, 22 g / g or more, 24 g / g or more, or 25 g / g or more. The method for measuring the CRC and AAP (0.3 psi) is not particularly limited, and they can be measured, for example, by the method described in the Examples below.
[0132] In one embodiment of the present invention, the "CRC" is an abbreviation for "Centrifuge Retention Capacity" and indicates the absorption capacity (unit: g / g) of a water absorbent resin (for example, the recycled water absorbent resin and the recycled water absorbent resin composition, etc.) for 30 minutes under no pressure for a 0.90 mass% sodium chloride aqueous solution. The method for measuring the "CRC" may be a known method and is not particularly limited. Specifically, the method for measuring the CRC described in the Examples may be used. In the above-mentioned method for measuring the CRC, the water absorbent resin may be a water absorbent resin composition containing adsorbent particles in addition to the water absorbent resin.
[0133] In one embodiment of the present invention, the "AAP (0.3 psi)" is an abbreviation of "Absorption Against Pressure" and indicates the absorbency (unit: g / g) of a water absorbent resin against a 0.90 mass% sodium chloride aqueous solution under a pressure of 0.3 psi. The method for measuring the "AAP (0.3 psi)" may be a known method and is not particularly limited. Specifically, the method for measuring the AAP (0.3 psi) described in the examples may be used. In the above-mentioned method for measuring the AAP (0.3 psi), the water absorbent resin may be a water absorbent resin composition containing adsorbent particles in addition to the water absorbent resin.
[0134] The present invention may also include the following inventions [1] to
[10] . [1] A recycled water-absorbent resin composition comprising a recycled water-absorbent resin containing, as at least a part of a raw material, a used water-absorbent resin and / or a solubilized product thereof, and adsorbent particles. [2] The BET specific surface area of the adsorbent particles is 200 m 2 / g or more, 3000m 2 / g or less of the recycled water absorbent resin composition according to [1]. [3] The recycled water absorbent resin composition according to [1] or [2], wherein the adsorbent particles include activated carbon. [4] The recycled water-absorbing resin composition according to any one of [1] to [3], further comprising a chelating agent. [5] The recycled water-absorbing resin composition according to any one of [1] to [4], further comprising a reducing agent. [6] The recycled water-absorbing resin composition according to any one of [1] to [5], further comprising inorganic fine particles. [7] The recycled water absorbent resin composition according to any one of [1] to [6], wherein the adsorptive particles contain an antibacterial metal. [8] The recycled water absorbent resin composition according to any one of [1] to [7], wherein the recycled water absorbent resin has a 16-hour water soluble component amount of 30 mass % or less. [9] A method for producing the recycled water-absorbing resin composition according to any one of [1] to [8], A method for producing a recycled water absorbent resin composition, comprising a mixing step of mixing the recycled water absorbent resin with the adsorbent particles.
[10] A gel drying step of drying the particulate hydrogel to obtain a dry polymer, By the end of the gel drying step, the used water absorbent resin and / or its solubilized material is provided as at least a part of the raw material of the recycled water absorbent resin; The method for producing a recycled water absorbent resin composition according to [9], wherein the mixing step is carried out after the gel drying step is completed.
[0135] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES
[0136] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the present invention is not limited to these examples. Examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention.
[0137] (Evaluation method) The physical properties of the water-absorbent resins and water-absorbent resin compositions obtained in Production Example 1, Comparative Examples 1 to 3, and Example 1 were measured and evaluated by the methods shown below.
[0138] (a) CRC (ERT441.1-99) 0.200 g of the water-absorbent resin or water-absorbent resin composition was uniformly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Industrial Co., Ltd., product name: Heatlon Paper, model: GSP-22) and heat-sealed, and then immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag was pulled out and drained for 3 minutes at a centrifugal force (250 G) described in ERT441.2-02 using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122), and the mass W1 (g) of the bag was measured. In addition, the same operation was performed without using the water-absorbent resin, and the mass W0 (g) at that time was measured. Then, from these W1 and W0, the CRC (centrifuge retention capacity) was calculated according to the following formula (1).
[0139] CRC(g / g)=[(W1-W0) / (mass of water-absorbent resin or water-absorbent resin composition)]-1...Equation (1) (b) AAP0.3 (NWSP 242.0.R2(15)) AAP0.3 was measured in accordance with NWSP 242.0.R2(15) except that the pressure condition was changed from 0.7 psi to 0.3 psi. Specifically, a large excess of 0.9 mass% sodium chloride aqueous solution was used, and 0.9 g of the water absorbent resin or water absorbent resin composition was subjected to pressure of 2.07 kPa (21 g / cm) for 1 hour. 2 After swelling under a pressure of 0.2 psi (0.3 psi), the AAP (absorbency against pressure) was measured.
[0140] (c) Coloration evaluation of recycled water absorbent resin composition (YI value / yellowness index) The color evaluation of the water absorbent resin produced in Reference Example 1 and the recycled water absorbent resin compositions produced in Comparative Examples 1 to 3 and Example 1 was carried out using a spectrophotometer (Spectrophotometer SE7700) manufactured by Nippon Denshoku Industries Co., Ltd. Reflection measurement was selected as the measurement setting condition, and the measurement diameter was LAV (28 mm). In addition, the attached 35Φ×15H round cell, 35Φ×15H cell case, and standard white board for powder were used. Under the conditions of room temperature (within the range of 20°C to 25°C) and humidity of 50 RH%, the YI value (Yellow Index) was measured with the spectrophotometer. In addition, the color tone (color, presence or absence of yellowing, etc.) of the recycled water absorbent resin compositions produced in Comparative Examples 1 to 3 and Example 1 was visually confirmed.
[0141] (d) 16-hour water-soluble component amount (ERT470.1-99) The amount of 16-hour water-soluble component of the water absorbent resin produced in Reference Example 1 and the recycled water absorbent resin compositions produced in Comparative Examples 1 to 3 and Example 1 was determined in accordance with ERT470.1-99 by stirring 1.0 g of the water absorbent resin or the water absorbent resin composition in 200 ml of physiological saline for 16 hours, and determining the water-soluble polymer content (mass%) in the filtrate by pH titration.
[0142] (e) Odor sensory evaluation 1 g of the recycled water absorbent resin composition produced in each of Comparative Examples 1 to 3 and Example 1 was swelled 20 times with physiological saline at 37°C in a 200 ml sealed container. After leaving it at 37°C for 1 hour, the lid of the container was opened, and the odor was smelled at a position about 3 cm from the top of the container, and an odor sensory evaluation of each recycled water absorbent resin composition was performed. The odor sensory evaluation was evaluated on a three-level scale: + (good), - (slightly bad), and -- (bad).
[0143] (f) Urine tolerance evaluation 1 g of the recycled water absorbent resin composition produced in each of Comparative Examples 1 to 3 and Example 1 was swelled 20 times in a 200 ml sealed container with physiological saline (temperature: 37°C) containing 0.05 mass% L-ascorbic acid. After 16 hours, the container containing each swollen recycled water absorbent resin composition (gel) was tilted 90° to check the state (fluidity) of the gel. The urine resistance of the recycled water absorbent resin composition was evaluated based on the criteria shown in Table 1.
[0144] [Table 1]
[0145] [Production Example 1] A reaction vessel was charged with 244.9 g of acrylic acid, 1.07 g (0.060 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 103.7 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 389.5 g of deionized water, and the mixture was mixed to prepare an aqueous monomer solution (a').
[0146] Next, the monomer aqueous solution (a') was cooled while stirring. When the liquid temperature reached 40.0°C, 100.9 g of a 48.5 mass% aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (a). At this time, the temperature of the monomer aqueous solution (a) rose to 78.2°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5 mass% aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved to form a transparent homogeneous solution.
[0147] Next, 12.1 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous solution of monomer (a), and the mixture was immediately poured into a stainless steel bat-shaped container (bottom surface 340×340 mm, height 25 mm, inner surface; Teflon (registered trademark) coating) in an open-air system. The time from the start of the second stage neutralization to the pouring of the aqueous solution of monomer (a) into the bat-shaped container was 55 seconds, and the bat-shaped container was heated using a hot plate until the surface temperature reached 40° C. The polymerization reaction started 60 seconds after the aqueous solution of monomer (a) was poured into the bat-shaped container. The polymerization reaction proceeded with the resultant polymer expanding and foaming in all directions while generating water vapor, and then the polymer shrunk to a size slightly larger than the bat-shaped container. After 3 minutes had passed from the start of the polymerization reaction, a hydrous gel-like crosslinked polymer (hereinafter referred to as "hydrous gel") (1) was taken out. The series of operations was carried out in an open-air system.
[0148] The hydrogel (1) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm. The crushed hydrogel (1) was then spread on a 50-mesh wire net and dried with hot air at 190°C for 60 minutes.
[0149] Next, the hot air dried hydrogel (1) was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized water absorbent resin precursor (1).
[0150] 100 parts by mass of the obtained water absorbent resin precursor (1) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water, and the mixture was subjected to a heat treatment at 100°C for 45 minutes.
[0151] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water absorbent resin (1). The obtained water absorbent resin (1) had a CRC of 34.1 g / g, an AAP0.3 of 29.4 g / g, and a YI value (yellowness index) of 10.8.
[0152] [Comparative Example 1] In a reaction vessel equipped with a stirrer, 200 g of the water absorbent resin (1) obtained in Production Example 1 was placed, and 6,000 g of artificial urine (urea: 1.9 mass%, sodium chloride: 0.80 mass%, magnesium chloride hexahydrate: 0.10 mass%, calcium chloride dihydrate: 0.10 mass%, ion-exchanged water: 97.1 mass%) was added thereto, and the mixture was left for 24 hours to prepare a simulated used water absorbent resin (1).
[0153] Next, 10,000 g of ethanol was added to the reaction vessel, and the mixture was stirred for 15 minutes to perform a dehydration operation of the simulated used water absorbent resin (1). The contents of the reaction vessel were then filtered through a stainless steel wire mesh with a mesh size of 100 mesh (150 μm) to obtain a filtrate (1). The solid content of the filtrate (1) was 24.4% by mass. 800 g of the obtained filtrate (1) was continuously put into a meat chopper, pulverized, and then dried in an oven at 190° C. for 2 hours to obtain a dried product (1).
[0154] Next, the dried material (1) was pulverized using a vibration mill and then classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain a recycled water-absorbent resin precursor (1) in an irregularly pulverized form.
[0155] A surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water was uniformly mixed with 100 parts by mass of the obtained recycled water absorbent resin precursor (1), and the mixture was subjected to a heat treatment at 100° C. for 45 minutes to obtain a recycled water absorbent resin (1). The obtained recycled water absorbent resin (1) was used as a comparative recycled water absorbent resin composition (1).
[0156] The comparative recycled water absorbent resin composition (1) thus obtained had a CRC of 34.6 g / g, an AAP0.3 of 29.6 g / g, and a YI value (yellowness index) of 23.9. In addition, the comparative recycled water absorbent resin composition (1) was confirmed to have a yellowish color.
[0157] [Comparative Example 2] In Comparative Example 1, the same operation as in Comparative Example 1 was carried out, except that 17.7 g of an aqueous hydrogen peroxide solution having a concentration of 0.50 mass% as a bleaching agent was continuously added to the meat chopper when 800 g of the filtrate (1) was continuously added to the meat chopper, to obtain a recycled water absorbent resin (2). The amount of hydrogen peroxide used (added amount) was 17.7 × 0.50 × 10 -2 =8.85×10 -2 g. The obtained recycled water absorbent resin (2) was used as a comparative recycled water absorbent resin composition (2). The solid content of the obtained comparative recycled water absorbent resin composition (2), that is, the ratio of the amount of hydrogen peroxide used to the total mass of the recycled water absorbent resin (2) and hydrogen peroxide as an additive (unit: mass%) was 0.05 mass%.
[0158] The comparative recycled water absorbent resin composition (2) thus obtained had a CRC of 34.3 g / g, an AAP0.3 of 29.3 g / g, and a YI value (yellowness index) of 20.0. In addition, the comparative recycled water absorbent resin composition (2) was confirmed to have a yellowish color.
[0159] [Comparative Example 3] In Comparative Example 1, the same operation as in Comparative Example 1 was performed except that 19.5 g of a 30 mass% aqueous hydrogen peroxide solution was continuously added as a bleaching agent to the meat chopper when 800 g of the filtrate (1) was continuously added to the meat chopper, to obtain a recycled water absorbent resin (3). The amount of hydrogen peroxide used (added amount) was 19.5 g x 30 x 10 -2 = 5.85g. The solid content of the obtained comparative recycled water absorbent resin composition (3), that is, the ratio of the amount of hydrogen peroxide used to the total mass of the recycled water absorbent resin (3) and hydrogen peroxide as an additive (unit: mass%) was 3.0 mass%. The obtained recycled water absorbent resin (3) was used as the comparative recycled water absorbent resin composition (3).
[0160] The comparative recycled water absorbent resin composition (3) thus obtained had a CRC of 45.2 g / g, an AAP0.3 of 11.8 g / g, and a YI value (yellowness index) of 11.3. The comparative recycled water absorbent resin composition (3) was white in color with no yellowing observed.
[0161] [Example 1] The recycled water absorbent resin (1) obtained in Comparative Example 1 was mixed with activated carbon (manufacturer: MC Evatec Co., Ltd., product name: Maxsorb MSP-20X (specific surface area: 2,300 m) 2 After adding 0.5% by mass of activated carbon (1.0 g / g), the two were thoroughly mixed. Specifically, the activated carbon was added to the recycled water absorbent resin (1) produced in the reaction vessel equipped with the stirrer in Comparative Example 1 so that the amount of the activated carbon used (unit: mass%) with respect to the total mass of the recycled water absorbent resin (1) and the activated carbon was 0.5% by mass. Next, in the reaction vessel equipped with the stirrer, the water absorbent resin obtained by the above operation was mixed with the recycled water absorbent resin (1) and the activated carbon by stirring at a stirring speed of 100 rpm for 15 minutes to produce a mixture (composition). The produced mixture (composition) was designated as a recycled water absorbent resin composition (1). The recycled water absorbent resin composition (1) had a CRC of 34.3 g / g and an AAP0.3 of 29.3 g / g. The color of the recycled water absorbent resin composition (1) was a clean black color overall.
[0162] [result] The physical properties of the recycled water absorbent resin (1), the comparative recycled water absorbent resin compositions (1) to (3), and the recycled water absorbent resin composition (1) produced in Production Example 1, Comparative Examples 1 to 3, and Example 1 were measured and evaluated using the above-mentioned evaluation methods. The results are shown in Table 2 below.
[0163] [Table 2]
[0164] [summary] The points that can be understood from the above descriptions of Comparative Examples 1 to 3 and Example 1, and the description of Table 2, are shown below.
[0165] The comparative recycled water absorbent resin composition (1) obtained in Comparative Example 1 was the recycled water absorbent resin (1) itself, without the addition of additives such as bleaching treatment during the manufacturing process. The comparative recycled water absorbent resin composition (1) had a higher (worsened) YI value (Yellow-Index) and yellowing compared to the water absorbent resin (1) obtained in Manufacturing Example 1. Therefore, it was found that the recycled water absorbent resin composition produced without the addition of additives such as bleaching treatment during the manufacturing process is undesirable from the viewpoint of hygiene, since it reminds one of the remaining urine.
[0166] In Comparative Example 2 and Comparative Example 3, a bleaching agent, hydrogen peroxide, was added in the production process so that the content (unit: mass%) relative to the mass of the solid content of the produced recycled water absorbent resin composition was 0.05 mass% (Comparative Example 2) and 3.0 mass% (Comparative Example 3), and a bleaching treatment was performed to produce comparative recycled water absorbent resin compositions (2) and (3). Here, the YI value of the comparative recycled water absorbent resin compositions (2) and (3) is lower (improved) compared to the comparative recycled water absorbent resin composition (1). However, the comparative recycled water absorbent resin composition (2) was found to be yellowed, indicating that bleaching was insufficient. The comparative recycled water absorbent resin composition (3) was bleached sufficiently, but compared to the comparative recycled water absorbent resin composition (1), an increase in the amount of water-soluble components, deterioration in urine resistance, and a decrease in AAP0.3 occurred. From the above, it has been found that in a manufacturing method of a recycled water absorbent resin composition in which bleaching is carried out by adding a bleaching agent in the manufacturing process, since the bleaching agent acts as a decomposing agent for the water absorbent resin, when the amount of the bleaching agent added is increased so as to exhibit a sufficient bleaching effect, deterioration of the properties of the recycled water absorbent resin composition occurs, such as an increase in the amount of water-soluble components, deterioration in urine resistance, and a decrease in AAP0.3.
[0167] On the other hand, in Example 1, a recycled water absorbent resin composition (1) was produced by using activated carbon, which is an adsorbent particle, instead of a bleaching agent. Thus, the recycled water absorbent resin composition (1) contains a recycled water absorbent resin made of a used water absorbent resin and / or a solubilized product thereof as at least a part of the raw material, and adsorbent particles, and corresponds to the recycled water absorbent resin composition of the present invention. In addition, the manufacturing method of the recycled water absorbent resin composition (1) in Example 1 corresponds to the manufacturing method of the recycled water absorbent resin composition of the present invention. Compared with the comparative recycled water absorbent resin composition (3), the recycled water absorbent resin composition (1) avoids deterioration of the characteristics of the recycled water absorbent resin composition, such as an increase in the amount of water-soluble components and deterioration in urine resistance. In addition, the appearance (color) of the recycled water absorbent resin composition (1) is a clean black color, and yellowing was not confirmed. Furthermore, compared with the comparative recycled water absorbent resin composition (1), i.e., the recycled water absorbent resin (1), the urine resistance of the recycled water absorbent resin composition (1) is improved, and the result of the odor sensory evaluation is also improved, so that the problem of odor generation is less likely to occur. From the above, it was found that the recycled water absorbent resin composition of the present invention, by containing adsorbent particles such as activated carbon, is less likely to cause odor generation, color deterioration, and water absorption performance deterioration, and is also less likely to cause urine resistance and an increase in the amount of water soluble components. Also, it was found that the manufacturing method of the recycled water absorbent resin composition of the present invention, by including a mixing step of mixing the recycled water absorbent resin and the adsorbent particles, can produce a recycled water absorbent resin composition that is less likely to cause odor generation, color deterioration, and water absorption performance deterioration, and is also less likely to cause urine resistance and an increase in the amount of water soluble components.
[0168] In addition, the activated carbon, which is the adsorbent particles, is a cheap and safe material. Therefore, when the activated carbon is used as the adsorbent particles in the recycled water absorbent resin composition and the manufacturing method of the recycled water absorbent resin composition of the present invention, it can be understood that the various problems (such as deterioration of color due to coloring, odor generation, deterioration of characteristics such as water absorption performance, balance between recycled resources (recycling cost) and consumed resources, etc.) that have occurred in the conventional recycled water absorbent resin can be solved at once. [Industrial Applicability]
[0169] The recycled water absorbent resin composition and the manufacturing method of the recycled water absorbent resin composition according to one embodiment of the present invention can be utilized for manufacturing absorbent articles which are less susceptible to odor generation, deterioration in color and deterioration in water absorption performance, and are also less susceptible to deterioration in urine resistance and increase in the amount of water-soluble components.
Claims
1. A recycled water-absorbent resin composition comprising a recycled water-absorbent resin containing, as at least a part of a raw material, a used water-absorbent resin and / or a solubilized product thereof, and adsorbent particles.
2. The BET specific surface area of the adsorbent particles is 200 m 2 / g or more, 3000m 2 The recycled water-absorbing resin composition according to claim 1, wherein the water-absorbing resin composition has a water-absorbent property of 0.1 to 1.0% by mass.
3. 2. The recycled water absorbent resin composition of claim 1, wherein the adsorbent particles comprise activated carbon particles.
4. The recycled water absorbent resin composition according to claim 1, further comprising a chelating agent.
5. The recycled water-absorbing resin composition according to claim 1, further comprising a reducing agent.
6. The recycled water-absorbing resin composition according to claim 1, further comprising inorganic fine particles.
7. 2. The recycled water absorbent resin composition of claim 1, wherein the adsorbent particles include an antibacterial metal.
8. The recycled water absorbent resin composition according to claim 1, wherein the recycled water absorbent resin has a 16-hour water soluble component amount of 30 mass % or less.
9. A method for producing the recycled water-absorbing resin composition according to any one of claims 1 to 8, A method for producing a recycled water absorbent resin composition, comprising a mixing step of mixing the recycled water absorbent resin with the adsorbent particles.
10. A gel drying step of drying the particulate hydrogel to obtain a dry polymer, By the end of the gel drying step, the used water absorbent resin and / or its solubilized material is provided as at least a part of the raw material of the recycled water absorbent resin; The method for producing a recycled water-absorbing resin composition according to claim 9, wherein the mixing step is carried out after the gel drying step is completed.
Citation Information
Patent Citations
Regeneration method for water absorbing resin, and water absorbent
JP2003326161A
Method for decomposing water-absorbing polymer, method for producing recycle pulp, and water-absorbing polymer decomposer kit
JP2019131789A
Processing method of used sanitary articles
JP2020049398A
Method for producing water-absorbing resin composition
JP2023038963A
Method for treating water-absorbing resin composition
JP2023038978A